Empowerment or Added Burden? A Narrative Analysis of Left-Behind Wives in Male Migrant Households in Kathmandu Valley, Nepal - Shrestha, Nishtha; Gurung, Dil Bahadur; Subedi, Madhusudan (Dhaulagiri Journal of Sociology and Anthropology, 2026)
Male migration has become an articulating socioeconomic trend in Nepal, reshaping household power dynamics and prompting shifts in women’s roles and responsibilities. This research explores how left-behind wives understand and experience their own empowerment and how they cope with or negotiate the disparity between their perception and the reality of empowerment. A narrative research design is applied, and a total of thirteen left-behind women were selected using purposive and snowball sampling techniques. The selected participants were interviewed using semi-structured interview questions. Interviews were transcribed, coded, and thematically analyzed. It is found that all participants take on increased responsibilities after their husbands’ migration abroad, and experience varying degrees of perceived empowerment. Factors that influence empowerment include family support, personal education, skills, and community networks. While some participants report increased decision-making authority and confidence, others have experienced symbolic empowerment that is limited by patriarchal culture, indicating an added burden rather than actual empowerment. Strategies for coping included emotional regulation, open communication, incremental economic efforts, and subtle subversion of dominant norms and values within their cultural boundaries. These findings indicate that empowerment occurs at multiple levels, depending on context, family structure, and social factors.